Health risk/benefit information for consumers of fish and shellfish: FishChoice, a new online tool. (June 2017) - Vilavert, Lolita; Borrell, Ferran; Nadal, Martí; Jacobs, Silke; Minnens, Fien; Verbeke, Wim; Marques, António; Domingo, José Luis
Abstract: It is well known that due to the content in omega-3 fatty acids, consumption of fish and shellfish is beneficial for human cardiovascular health. However, a number of recent studies have shown that fish consumption may be also a potential dietary source of exposure to various environmental pollutants with well-known potential adverse effects on human health. Moreover, there is still a lack of information regarding levels of emerging contaminants in fish and shellfish, in particular among consumers and stakeholders. Within the ECsafeSEAFOOD FP7 project, a wide variety of emerging contaminants including brominated flame retardants, pharmaceuticals, perfluoroalkyl substances, musk fragrances, polycyclic aromatic hydrocarbons, UV-filters and endocrine disruptors, as well as inorganic arsenic and methylmercury, were analyzed in fish and shellfish samples collected all over the European Union. These data, together with those regarding nutrient concentrations from different European food composition databases, were integrated into a new online tool, called FishChoice. In this paper, we report how FishChoice was designed and present its main improvements compared to previous tools or software programs, in terms of selected pollutants, number of species, and specific recommendations for an optimal consumption of fish and shellfish. Highlights: Dietary assessment methods using technology are preferred by young generations. Fish consumption is a key dietary source of exposure to environmental pollutants. ECsafeSEAFOOD was aimed at analyzing the levels of emerging pollutants in seafood. FishChoice is an online tool to balance benefits and risks of seafood consumption.